Regulating the Vascular Cambium: Do Not Forget the Vascular Ray Initials and Their Derivatives - Lev-Yadun, Simcha (Plants (Basel), 2025)
The secondary lateral meristem—the vascular cambium (hereafter cambium)—is the largest meristem of the plant kingdom. It is almost always composed of two types of stem cells: (1) the axial (fusiform) initials, the most common and better known and studied, and (2) the ray initials that give rise to the vascular rays (hereafter rays), i.e., the radial component of the secondary xylem and phloem, which are less common and much less studied, and in many studies ignored. There is great flexibility in switching from axial initials to ray initials and vice versa. Ray initials commonly compose ca. 10–40% of the cambium of mature tree trunks, but nothing or very little in typical young model plants used for molecular cambial studies, such as Arabidopsis thaliana and young internodes of Populus spp. cuttings. I suggest paying more attention to the regulation of the differentiation of ray initials and their derivatives, and to the little-known complicated relations between the axial and ray cambial initials when they contact each other, as well as the special development of pits in their derivatives in cambial molecular studies by using mature trunks of various large woody plants rather than studying A. thaliana or young internodes of Populus cuttings.